Diplomacy and Treaty Governance by Indonesia as Norm-Shaping Practices to Align National Interests of Indonesia - Ifdal, Abdurrahman Al-Fatih (JURNAL HUBUNGAN LUAR NEGERI, 2024)
Treaty governance in Indonesia is central to both the promotion of rule of law through diplomacy and the advancement of predictability in international relations, particularly through diplomacy conducted by Indonesia. By integrating domestic treaty governance with international legal standards, Indonesia enhances global legal stability and certainty. This approach highlights Indonesia’s commitment to maintaining legal principles, reinforcing its role as a key player in global diplomacy and international governance. This article hopes to thoroughly research on the practices considered norm-shaping as seen through Indonesia’s diplomacy and treaty governance laws, with a particular focus on the Minister of Foreign Affairs Regulation No. 4 of 2023 on the Governance of International Treaty Documents and other related regulations. In addition, this article seeks to identify the key norms regulating treaty governance in Indonesia as further established through Indonesia’s engagements in the international community. This article argues that treaty governance should not merely be seen as a monitoring mechanism but as a tool for shaping norms, promoting predictability in alignment with Indonesia’s national interests. This article then proposes a takeaway for Indonesia to identify its national laws in order to explicitly locate the treaty governance norms, in which Indonesia’s diplomacy must refer to. This strategic approach allows Indonesia to promote consistency and legal certainty globally while aligning international norms with its domestic priorities.